THE ROLE OF MODERN MARKETS IN INFLUENCING LIFESTYLES IN INDONESIA - Achmad Suryana; Mewa Ariani; Erna M Lokollo (Jurnal Penelitian dan Pengembangan Pertanian, 2008)
Globalization in trade and information system, the fast growth of modern markets and fast food outlets, and fast invasion of food advertisements are currently occurred in Indonesia. The paper reviewed the impacts of modern markets, fast food outlets, and advertisements on lifestyle, especially in eating, of Indonesian people. The results showed that the number of minimarkets and supermarkets selling various goods, food, and beverages increased significantly in Indonesia. Moreover, there is open information which advertises many kinds of prepared food and beverages. The impacts are the change in eating lifestyle as part of Indonesian people lifestyle. This is shown by the increasing share of prepared food and beverages expenditure to total expenditure, especially in urban area. Changes in diet and eating lifestyle in society can be seen as the opportunity for food and beverages industries to expand their products and markets.Keywords: Modern markets, lifestyles, food expenditures, fast food and beverages, consumers, Indonesia